LEGAL REGULATION OF REMOTE SENSING OF THE EARTH FROM SPACE - Netska, Liubov; Brusylo, Olena; Khomusko, Elyzaveta (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is a comprehensive legal analysis of remote sensing of the Earth taking into account the current state of national and international legislation, identifying gaps in the legal regulation of this sphere of relations and developing proposals for its improvement. Research methods: the research process used a combination of general scientific and special legal methods. In particular, the methods of analysis and synthesis were used to study the sources of law; the comparative legal method - to analyze international and national legislation; a systemic approach - to consider remote sensing of the Earth as an element of a complex system of space law; as well as a formal-legal method for studying legal norms regulating the sphere of remote sensing of the Earth. Results: the legal aspects of remote sensing of the Earth from space as a component of space activities were analyzed. Taking into account the rapid development of satellite technologies, the globalization of space projects, and the growth in the volume of data obtained, attention is focused on the legal regulation of access to remote sensing data of the Earth, protection of national interests, preservation of confidentiality and international cooperation in the process of remote sensing of the Earth. The main legal challenges in the use of remote sensing data are identified, and ways to improve national and international legislation are proposed. Discussion: principles governing remote sensing of the Earth; legal support for activities related to remote sensing of the Earth; legal regime of received data from remote sensing of the Earth; the relationship between technical regulation and legal regulation of remote sensing of the Earth; features of legal regulation of remote sensing of the Earth in Ukraine.